Energy Transition for rural development: A preliminar case study in Colombia for improving artisanal fishing - Bueno Lopez, Maximiliano; Rengifo Ordoñez, Monica Tatiana; Chacón Campo, Diego; Tocancipá-Falla, Jairo; Osorio Arias, Andres (Scientia et Technica, 2024)
According to the Food and Agriculture Organization of the United Nations (FAO), artisanal fishing relates to the use of small fishing vessels for short fishing trips devote to capture fish for their consumption and also for local marketing. This is a process that requires the use of energy in its different phases, from the boat for navigation to the refrigeration center for storage. The energy used for this process normally comes from fossil fuels, which generates an impact from the environmental point of view by the footprint left by the boats, added by the lack of economic resources for the purchase of fuel required by the engines, hampering the daily work of fishermen. The International Renewable Energy Agency (IRENA) defines energy transition as the pathway towards the transformation of the global energy sector from fossil-based to zero-carbon by the second half of this century. The energy transition seeks the decarbonization of the economy and provides opportunities to reduce dependence on fossil fuels. This paper reviews some basic concepts necessary to understand the process to reduce the consumption of fossil fuels in fishing operations from the perspective of the energy transition. Technological, environmental, and socio-economic factors are considered to promote responsible fishing in rural areas coastlines in Colombia. A case study in the municipality of Guapi (province of Cauca, Colombia) is considerate.